AB0724 Safety, pharmacokinetics, and pharmacodynamics of a human anti-IL6 monoclonal antibody PF-04236921 in healthy subjects. (23rd January 2014) - Fogel, R.; Sridharan, S.; Li, C.; Bradley, J.; Riese, R.; Labadie, R.; Menon, S.; Gupta, P.; Krishnasawami, S.; Beebe, J.
Abstract : Background: PF-04236921 is a fully human monoclonal antibody that binds with high affinity to the human interleukin-6 (IL6) ligand, and neutralizes its activity. It is a new subcutaneous (SC) biological therapy in development for inflammatory diseases. Objectives: To evaluate the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) of PF-04236921 following single intravenous (IV) doses and single SC doses in healthy adult volunteers (HVs). Methods: The first in human Study B0151001 was conducted in 48 HVs who, in ascending IV dose cohorts, were randomly assigned to receive PF-04236921 (7, 22, 44, 118, 284, 500, and 700 mg) or placebo. Adverse events (AEs) were monitored throughout the study. Serum samples were collected to measure PF-04236921 concentrations, C-reactive protein (CRP), total IL6 as a target biomarker, and antibodies to PF-04236921. Subjects were followed until their serum levels of PF-04236921 were undectable. Non-compartmental analysis and population PK modeling were performed to characterize the PK of PF-04236921. Population PK/PD modeling was conducted to characterize the CRP response. A single SC dose of PF-04236921 (200 mg) was administered to 10 HVs in Study B0151004 with similar assessments. Results: Overall, PF-04236921 was generally well tolerated. There was no apparent increase in the frequency or distribution of AEs including infections or laboratory abnormalities with increasing dose. Expected minor elevations in serum lipids, and transient reductions in circulating neutrophil counts were observed, but were not associated with infections or other adverse events. Three serious AEs in two subjects were reported in Study B0151001. No serious AEs were reported in Study B0151004. No antidrug antibodies to PF-04236921 or injection site reactions were observed. Following IV administrations, exposure (Cmax and AUC(0, ∞)) increased approximately dose-proportionally. Terminal half-life in HVs was approximately 51 days. Comparison of dose-normalized exposure suggested SC bioavailability is >90%. A two-compartment model adequately described the PK of PF-04236921 following IV administration. Population estimates for the clearance (CL), the central volume of distribution ( V 1), the inter-compartmental clearance (Q) and the peripheral volume of distribution ( V 2) were 0.00416 L hr -1, 3.23 l, 0.0215 L hr -1 and 3.72 L hr -1, respectively. Compared with placebo subjects, a sustained decrease from baseline in CRP and an increase in total IL-6 were observed in treated dose groups. An inhibitory indirect response PD model described the relationship between PF-04236921 concentrations and CRP suppression in HVs with a population estimate of EC50 of 422 ng/ml. Conclusions: PF-04236921 is being developed as an IL6 inhibitor for inflammatory diseases. PF-04236921 demonstrated a well-tolerated safety profile, no positive antibodies to PF-04236921 in HVs and desirable PK and PD properties supporting sustained target inhibition. Phase 2 studies using the SC formulation of PF-04236921 are currently ongoing. Disclosure of Interest: R. Fogel Employee of: Pfizer, S. Sridharan Employee of: Pfizer, C. Li Employee of: Pfizer, J. Bradley Employee of: Pfizer, R. Riese Employee of: Pfizer, R. Labadie Employee of: Pfizer, S. Menon Employee of: Pfizer, P. Gupta Employee of: Pfizer, S. Krishnasawami Employee of: Pfizer, J. Beebe Employee of: Pfizer